1995
DOI: 10.1007/bf02515818
|View full text |Cite
|
Sign up to set email alerts
|

Interannual fluctuations in recruitment and growth of the sardine, Sardinops melanostictus, in the sea of Japan and adjacent waters

Abstract: Recruitment and growth of the sardine Sardinops melanostictus fluctuated markedly in the Sea of Japan and adjacent waters between 1978 and 1993. Stock size was calculated using Virtual Population Analysis and average body length in each age class was determined by the number of annual rings on the scales. There is an inverse correlation between average water temperature at a depth of 50 m in the coastal area of the mainland of Japan in winter (January to March) and recruitment R defined as the number of indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(54 citation statements)
references
References 6 publications
0
52
2
Order By: Relevance
“…Catching large numbers of new recruits may result in a decrease in intraspecific competition, and hence faster growth rates, allowing fish to achieve maturation at younger ages (Watanabe et al, 2000;Watanabe and Yatsu, 2004). This density-dependent growth has been observed in other pelagic fishes such as Japanese sardine (Hiyama et al, 1995;Wada et al, 1995), Japanese Spanish mackerel (Kishida, 1990), and common squid (Kidokoro, 2001).…”
Section: Discussionmentioning
confidence: 84%
“…Catching large numbers of new recruits may result in a decrease in intraspecific competition, and hence faster growth rates, allowing fish to achieve maturation at younger ages (Watanabe et al, 2000;Watanabe and Yatsu, 2004). This density-dependent growth has been observed in other pelagic fishes such as Japanese sardine (Hiyama et al, 1995;Wada et al, 1995), Japanese Spanish mackerel (Kishida, 1990), and common squid (Kidokoro, 2001).…”
Section: Discussionmentioning
confidence: 84%
“…The shift to the anchovy regime (the second replacement) occurred in 1988. Low sardine recruitment was reported between 1988 and 1991 (Hiyama et al 1995;Ohshimo et al 2009;Tanaka et al 2010), whereas anchovy recruitment increased between 1987 and 1990 (Kuroda et al 2011). These opposite trends may have been caused by climate and climaterelated environmental changes (Ohshimo et al 2009;Sakuramoto et al 2010;Yatsu et al 2005).…”
Section: Discussionmentioning
confidence: 92%
“…This is also true for sardine and anchovy (Figure a,b), based on the apparent asymptotic patterns in the SSB–R relationships (Figure a), even with stronger environmental effects causing the observed high variability in the SSB–R relationships. Furthermore, density‐dependent effects on growth and maturation were reported for sardine at least (Hiyama et al, ; Kim et al, ; Ohshimo et al, ; Wada & Kashiwai, ).…”
Section: Discussionmentioning
confidence: 99%
“…The maturation rate for 1‐year‐old fish was assumed to be 10% during 1978–1993 (high‐biomass period), 20% during 1994–1997 (medium‐biomass period) and 50% during 1998–2015 (low‐biomass period) for sardine (Yukami et al, ), whereas it was assumed to be constant at 100% for anchovy (Kamimura et al, ). The assumption is not based on observations at a monthly basis but refers to previous observations (Hiyama, Nishida, & Goto, ; Ohshimo, Tanaka, & Hiyama, ; Wada & Kashiwai, ). Although the assumption could be a bias source in SSB and SSA estimates, a sensitivity analysis under different assumptions of maturation rate confirmed that the results of the test of density dependence in egg production were robust in the previous study (Takasuka et al, ).…”
Section: Methodsmentioning
confidence: 99%